Gastrointestinal functional disorders can benefit from the use of medical devices made of substances - Savarino, Vincenzo; Marabotto, Elisa; Zentilin, Patrizia; Furnari, Manuele; Bodini, Giorgia; Giovanni Giannini, Edoardo; Vincenzo Savarino, Edoardo (Frontiers in Drug Safety and Regulation, 2023)
Medical devices made of substances (MDMS) have recently gained great popularity in several specialties of internal medicine, including gastroenterology. In the last decades this discipline has known relevant advances in the cure of severe diseases, such as peptic ulcer, gastroesophageal reflux disease and chronic hepatitis C, thanks to the revolutionary development of new drugs able to act on single receptors changing a particular cell function or blocking microbial and viral replication. However, there are many gastroenterological illnesses that are difficult to treat with traditional medicinal products because of their complex and poorly known pathophysiology, which comprises altered motility, visceral hypersensitivity, gut dysbiosis, intestinal mild inflammation with impaired immune function, increased mucosal permeability and abnormal brain-gut interaction. They are mainly represented by esophageal functional disorders (reflux hypersensitivity, functional heartburn), functional dyspepsia, irritable bowel syndrome, functional constipation and functional diarrhea. Traditional drugs do not provide a definitive resolution of these disorders with a multifactorial pathogenesis and they can benefit from the use of MDMS, which seem to have the ability to act on different factors thanks to the synergistic action of their various components. International medical literature already reports many clinical trials performed with the well-known standards for evaluating their efficacy and safety in a great part of the above-mentioned conditions.